Asian and Asian American Representation in Selected American Films - Buryšková, Iva (Univerzita Pardubice, 2023)
This bachelor thesis deals with the topic of Asian and Asian-American representation in American film. It examines the development of the way Asians were and are treated by Westerners, namely Americans, the effect media has on general public and describes stereotypes, which are often associated with Asians. It then applies this information in the analysis of the two films My Geisha (1962) and Crazy Rich Asians (2018) and the way they approach Asian representation on the silver screen.
Zobrazení Asiatů a Američanů asijského původu ve vybraných amerických filmech
Keywords: Američané asijského původu; americké filmy; reprezentace; menšina; stereotypy; whitewashing; Asian Americans; American film; representation; minority; stereotypes; whitewashing